Accessibility of TV programs to persons with disabilities - Ćitić, Tatjana (Sociološki pregled, 2021)
The most modern media systems in television program production and placement have the obligation of ensuring program accessibility to persons with disabilities. While in some countries this obligation is defined through a certain minimum of adapted content, in Serbia there is a set of media laws only indicating the necessity of care for persons with difficulty in following the television program. The basic thesis of this paper is how program accessibility, and thus increased social inclusion through media content, may be improved through the development and greater presence of the existing services (subtitle, sign language, audio-description), as well as through the introduction of new services, based on the capacities offered by digital technology and application of artificial intelligence in content production and placement. The statistics shows that at least one in eighteen persons in Serbia has difficulty in following TV program due to vision or hearing impairment and therefore, in the absence of the tools ensuring accessibility, these persons are unable to get information, education and entertainment from the television program.